Problem-based Behavioral Science and Psychiatry - Guerrero, Anthony; Piasecki, Melissa (Springer New York : Imprint: Springer, 2008)
Problem-Based Behavioral Science and Psychiatry Edited by Anthony Guerrero, University of Hawaii, Honolulu Melissa Piasecki, University of Nevada, Reno In keeping with the growing emphasis on psychiatry in the medical school curriculum, problem-based learning (PBL) offers students a unique patient-centered, multidisciplinary approach to study and the synthesis of knowledge. The first text fully consistent with PBL models and methods, Problem-Based Behavioral Science and Psychiatry is a clinically robust resource for both the medical and the behavioral science student. Over 40 contributors, many themselves graduates of PBL medical schools, apply problem-based learning methods to specific psychiatric disorders, general clinical issues, and bedrock physician skills such as the intake interview and treatment planning. The book's fictional case vignettes illustrate typical patient scenarios, providing real-world context for content areas, and accompanying case diagrams show the relationships between patient behavior and underlying neurobiological structures. Each student-friendly section ends with helpful review questions. A sampling of the content areas covered: Childhood development and brain development. Major psychological illnesses, including personality, mood, anxiety, and psychotic disorders. Stress, substance abuse, and violence. Eating, sleep, and sexual disorders. Coping skills and treatment compliance. End-of-life care. PLUS chapters on cultural sensitivity, ethical concerns, and the physician/patient relationship. This book makes an excellent prep/review text for psychiatry residents preparing for the USMCE Step 3 exam and third- and fourth-year medical students preparing for the USMLE Step 1 and 2 exams, as well as being suited to graduate students in psychology or clinical social work. Problem-Based Behavioral Science and Psychiatry encourages lifelong learning and helps build the foundation for a lifelong career.